A Brief Rationale for MMT Arguments - Tanaka, Yasuhito (Issues in Social Science, 2024)
In this note we examine MMT (Modern Monetary Theory) arguments by a simple macroeconomic model without microeconomic foundation. Mainly we will show the following results. 1) In the underemployment case the national income is determined by the budget deficit. 2) In the full employment case we can define the budget deficit which is necessary and sufficient to achieve full employment. 3) The excessive budget deficit causes inflation. 4) We need budget deficit to achieve and maintain full employment under economic growth. 5) We can recover recession by the budget deficit which is larger than that when full employment is maintained. Also, we show that the budget deficit equals the increase in the savings between generations.